Armadilha macroeconômica e impactos sobre a dinâmica da dívida pública brasileira pós 1994 - Santos, Ana Carla (2011)
This study has as its main objective the study of the causal relationship between a set of macroeconomic and financial variables and the Public Debt, represented the Public Sector Net Debt, using the approach of multivariate regression model Self-Vector (VAR). Thus, we sougth to analyze the assumptions made by Correa and Biagi (2009), dealing about the growth of public debt to articulate financial factors linked to macroeconomic policy that interrelates financial openness, the volatile capital, high interet rates and the priority policy to fight inflation. The sample period includes the post form 1994 to 2010. Thus, for the proposed model, there was first the unit root test verifying that only two variables were not stationary, proceeding to theis use in first difference. Turthermore, it was tested for cointegration, resulting in failure to identify vector cointegrates, following to the application of VAR. Through Schwarz test, followed up to verify the selection criteria for the lag order of the variables in the matrix. Thus, based on these results, it became possible to say that the variables hava a behavior around a mean value, no significant structural breacks, which makes the design more robust. In arrays of contemporary relationships a significant relatioonship between the Public Debt and Public Debt. For other variables, the exchange rate, Aliens and Other Investments Other Investments Brazilian also had positive effects on the Public Debt. And, to a lesser extent, the variables Country Risk, Interesting Rate Long Term Selic rate, IPCA and Foreig Investiment in Portfolio. In the analysis of variance decomposition, the Public Debt demontrated hig explanatory power of more than 60% of its variation. This explanatory importance is followed by exchange and by interest. This result makes clear the determination of the decomposition of the forecast error as the impulse response function. Among the variables anlyzed, the Public Debt was the most impacted the Public Debt, showing its importance in the Brazilian economy.